FARMING SYSTEM ADAPTATION TO CLIMATE CHANGE IN ALGERIA: CHALLENGES AND STRATEGIES - Belguet Assia; Bouchareb Radia; Chafia Benider; Guendouz Ali (Natural Resources and Sustainable Development)
Africa faces significant challenges due to climate change, with rising temperatures, unpredictable rainfall patterns, and increased frequency of extreme weather events. Algeria, it’s one of the countries, is facing the pressing challenge of adapting its farming systems to the impacts of climate change. This paper provides an overview of the strategies and initiatives undertaken in Algeria to enhance agricultural resilience in the face of changing climatic conditions. The agriculture sector in Algeria is vital for food security and economic stability, yet it is highly vulnerable to the effects of climate change such as unpredictable rainfall patterns, increased temperatures, and extreme weather events. The Algerian government, in collaboration with various stakeholders, has implemented a range of adaptation measures. One key strategy has been the promotion of climate-smart agriculture practices, including the use of drought-resistant crop varieties, improved irrigation techniques, and conservation agriculture methods. Furthermore, investments in agricultural infrastructure, such as water storage facilities and efficient irrigation systems, have been crucial in mitigating the impacts of water scarcity and ensuring reliable access to water for farming activities. Power farmers with the knowledge and skills needed to adapt to changing conditions. These programs focus on climate information services, agro-ecological practices, and efficient use of inputs. The adaptation of farming systems to climate change in Algeria requires a multifaceted approach that integrates policy support, technological innovations, and community engagement. By building resilience at the farm level and enhancing adaptive capacity, Algeria aims to safeguard its agricultural sector and ensure food security for future generations